Breakage mechanisms of highly porous particles in 1D compression revealed by X-ray tomography. Issue 2 (29th June 2018) - Guida, G.; Casini, F.; Viggiani, G. M. B.; Andò, E.; Viggiani, G.
Abstract : Grain breakage affects a number of geotechnical engineering problems. In this research study, the breakage of an artificial, porous granular material (light-expanded clay aggregate (LECA)) has been studied in one-dimensional compression with both standard laboratory techniques and in situ X-ray tomography during loading. X-ray tomography has revealed that there is a wide distribution of internal porosity among LECA particles, and particle tracking has been used, for the first time, to give an objective measurement of each particle's life expectancy. Links between micro- and macro-scale quantities are discussed.